2009
DOI: 10.1002/mus.21564
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic neuropathy: Electrophysiological and morphological study of peripheral nerve degeneration and regeneration in transgenic mice that express IFNβ in β cells

Abstract: Diabetic neuropathy is one of the most frequent complications in diabetes but there are no treatments beyond glucose control, due in part to the lack of an appropriate animal model to assess an effective therapy. This study was undertaken to characterize the degenerative and regenerative responses of peripheral nerves after induced sciatic nerve damage in transgenic rat insulin I promoter / human interferon beta (RIP/IFNbeta) mice made diabetic with a low dose of streptozotocin (STZ) as an animal model of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Recently, Serafín et al [34] developed a model of diabetic neuropathy in 6-week-old rat insulin I promoter/human interferon-beta (RIP/IFN β ) transgenic ICR mice with a low dose of STZ injection (30 mg/kg BW) for 5 consecutive days. Additionally, in order to induce nerve damage, after 4 weeks of sustained hyperglycemia, the left sciatic nerve was exposed by blunt dissection and crushed at the femur major trochanter level for three times in succession for 30 seconds in anaesthetized animals when intact contralateral nerve was used as a control.…”
Section: Animal Models In Diabetic Neuropathymentioning
confidence: 99%
“…Recently, Serafín et al [34] developed a model of diabetic neuropathy in 6-week-old rat insulin I promoter/human interferon-beta (RIP/IFN β ) transgenic ICR mice with a low dose of STZ injection (30 mg/kg BW) for 5 consecutive days. Additionally, in order to induce nerve damage, after 4 weeks of sustained hyperglycemia, the left sciatic nerve was exposed by blunt dissection and crushed at the femur major trochanter level for three times in succession for 30 seconds in anaesthetized animals when intact contralateral nerve was used as a control.…”
Section: Animal Models In Diabetic Neuropathymentioning
confidence: 99%
“…Accounts of the traditional use of an antidiabetic plant in type 1 or type 2 diabetic patients provide an indication of the type of model (e.g., insulin dependent or noninsulin dependent) that might be suitable for initial investigation of hypoglycemic activity [1, 3, 78, 79, 88]. As it was noted previously, experimentally induced models of insulin-dependent diabetes are often not completely devoid of endogenous insulin.…”
Section: Right Model For Right Plantmentioning
confidence: 99%
“…However, many of these descriptions are anecdotal accounts of traditional usage, and fewer than half of these plants or plant extracts have received a thorough medical or scientific evaluation of their purported benefits. This paper reviews the preclinical in vivo methods and clinical procedures used to investigate the antidiabetic activity of plants and plant-derived extracts, including a consideration of the ethical issues affecting use of traditional plant treatments for diabetes [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported diabetic neuropathy resulted in abnormal deposits of laminin in human and animal models (8), but in contrast Hill et al reported that, in human diabetic neuropathy laminin content in diabetic and control nerves was not significantly different (6). Also Serafin et al (26) assessed laminin in peripheral nerves of STZ-induced diabetic mice, and reported that it did not differ in laminin expression in the diabetic and control nerves. These discrepancies are probably due to differences in experimental methods, in Serafin et al study (26), mice was made diabetic with a low dose of streptozotocin with a short study time period and in Hill et al study (6), duration of diabetes in diabetic patients was different.…”
Section: Discussionmentioning
confidence: 98%
“…Also Serafin et al (26) assessed laminin in peripheral nerves of STZ-induced diabetic mice, and reported that it did not differ in laminin expression in the diabetic and control nerves. These discrepancies are probably due to differences in experimental methods, in Serafin et al study (26), mice was made diabetic with a low dose of streptozotocin with a short study time period and in Hill et al study (6), duration of diabetes in diabetic patients was different. Diabetes duration and long-term hyperglycemia are the most important reasons for polyneuropathy (22).…”
Section: Discussionmentioning
confidence: 99%